2015
DOI: 10.3892/mmr.2015.3962
|View full text |Cite
|
Sign up to set email alerts
|

Yifei Xuanfei Jiangzhuo formula, a Chinese herbal decoction, improves memory impairment through inhibiting apoptosis and enhancing PKA/CREB signal transduction in rats with cerebral ischemia/reperfusion

Abstract: Apoptosis and the dysfunction of the cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA)/cAMP-responsive element binding protein (CREB) signaling pathway have a key role in memory impairment in vascular dementia (VaD), a challenging clinical problem. Yifei Xuanfei Jiangzhuo formula (YXJF), a Chinese herbal decoction, has been used to treat VaD in clinical practice and has produced positive outcomes; however, convincing evidence is currently lacking. The present study aimed to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies regarding learning memory behaviors have indicated that CREB, as 'the third messenger', is important in the long-term memory process (30)(31)(32). It is believed, as the optimal nuclear transcription factor, to adapt to external stimulus as well as long term memory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding learning memory behaviors have indicated that CREB, as 'the third messenger', is important in the long-term memory process (30)(31)(32). It is believed, as the optimal nuclear transcription factor, to adapt to external stimulus as well as long term memory.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and Bax are the two major factors influencing the regulation of apoptosis; Bcl-2 prevents the release of cytochrome C from mitochondria, and it also activates caspases to inhibit apoptosis. In contrast, Bax protein directly induces the release of cytochrome C from mitochondria into the cytoplasm, thereby promoting apoptosis [ 43 ]. To further explore the function of RSNP in inhibiting cell apoptosis, we performed Western blot and real-time Q-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Yifei Xuanfei Jiangzhuo Formula (YXJF) has the effects of nourishing and expelling the lungs, clearing the organs, reducing turbidity, ameliorating memory impairments in rats with cerebral ischemia/reperfusion, inhibiting hippocampal apoptosis in a dose-dependent manner, attenuating the increase in protein expression of Bcl-2-associated X protein and c-Jun, and reducing Bcl-2 protein expression in the hippocampal tissue of the rats ( Wu et al, 2015b ). Modified Dioscorea Pills (MDP) promotes the regeneration and repair of hippocampal neurons by inhibiting downregulation of the ERK5/BMK1 signaling pathway, improving disorder in the hippocampal tissue structure in VD model rats, and reducing apoptosis in hippocampal neurons, thereby improving learning ability and memory ( Li et al, 2020b ).…”
Section: Neuronal Apoptosis In Vdmentioning
confidence: 99%